PELATIHAN DIGITAL MARKETING BAGI PELAKU UMKM KUE TRADISIONAL DUSUN JUNTI KAUM - Eka Candra; Elvira Suryani; Purnama Putra (Universitas Islam 45 Bekasi, 2022)
The internet has been used by various circles of society, including Micro, small and medium Enterprises entrepreneurs in the regions. However, the lack of insight and education for Micro, Small and Medium Enterprises entrepreneurs causes not optimal use of the internet in supporting business processes in order to increase the profits achieved by Micro, Small and Medium Enterprises. One of the uses of the internet in business management is digital marketing. Digital Marketing is a form of marketing or promotion of a product using digital media or the internet with the aim of attracting consumers quickly. Based on the results of observations and interviews conducted, it was found that there were problems where MSME actors were still selling products manually and had not done marketing through digital marketing. The implementation method used is training with the aim of increasing the understanding of Micro, Small and Medium Enterprises of Traditional Cakes about digital marketing in Junti Kaum Hamlet. The activities include providing counseling on digital marketing to Micro, Small and Medium Enterprises, training on making digital stores and training in marketing publications. This activity is carried out as a form of community service through Real Work Lectures organized by the 45 Bekasi Islamic University Research and Service Institute.